Traditional practices for storage of wheat and maize grains in identified villages of Samastipur district Bihar, India - Rajak, Dinesh; Immanuel , Genitha (Journal of Postharvest Technology, 2022)
A survey was conducted on the traditional practices for the storage of Wheat & Maize grains in 15 villages of Samastipur districts in Bihar viz.Fulhara,  Ajana, Gopalpur, Maniarpur, Rampura, Ladaura, Birsingpur, Kalyanpur, Akbarpur, Pratapur, Basudevpur, Dhruvgama, Teera, Mirjapur, Kabargama of  Samastipur for the study. A pre drafted questionnaire was used to record the details of the storage practices. Information was collected from 90  farmers selected randomly from all these 15 villages. It was found that 16% of the farmers used all five storage modes like (Jute bag, Plastic bag, Mud  bin, Plastic container & Metal bin) for storage of grains while31%, 23%, 18% and 12%farmersuses four(Jute bag, Plastic bag, Plastic container & Metal  bin)three(Jute bag, Plastic bag & Mud bin) two (Jute bag & Plastic bag) and one (Jute bag)storage types respectively modes based on the availability.  The present study revealed that 28.89% farmers were using Jute Bags, 35.56 % farmers were using plastic bags, 6.66% farmers were using Mud bin,  8.89% farmers were using Plastic container and 20.00% farmers were using Metal bin. It was also observed that 6.66% farmers prefer to use Mud bin  (Khothi) made of clay. However, due to lack of space, immovable characteristics, lack of skilled person for construction of Khothi, now a days the use  of Mud bin hasbeen renounce by the farmers. Hence jute bag and plastic bags of good quality with 50 kg capacity need to made available for storage  of wheat and maize.
Keywords: Jute bag; metal bin; mud bin; plastic bag plastic container; storage modes